Peran Pendidikan Kewirausahaan di Perguruan Tinggi dalam Meningkatkan Daya Saing Mahasiswa dalam Memasuki Dunia Kerja - Hamdan, Hamdan (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Entrepreneurship education has become a primary focus for many higher education institutions in response to the increasingly complex demands of the job market and intensifying competition. Amid rapid technological advancements and digital transformation, skills such as adaptability, innovation, and risk-taking are highly valuable. The research aims to analyze the role of entrepreneurship education in higher education institutions in enhancing students' competitiveness in entering the workforce. This study utilizes a qualitative method, prioritizing literature analysis as the data source. Using databases like Google Scholar, articles are identified, filtered based on relevance, and analyzed inductively to extract and synthesize data. Validity is ensured through systematic documentation and triangulation. The research findings indicate that entrepreneurship programs significantly shape students' entrepreneurial attitudes and skills. Challenges include curriculum integration, soft skills development, and adaptation to technological advancements. The success of entrepreneurship programs is not only measured by the establishment of businesses but also their impact on society. Collaboration and continuous improvement are essential. Thus, entrepreneurship education in higher education institutions has the potential to enhance students' competitiveness. Efforts to improve the quality, relevance, and inclusivity of programs are crucial. These efforts are vital in shaping an innovative and influential entrepreneurial generation, overcoming challenges, and seizing opportunities in today's competitive business world